Comparative Study Of Learning Some Freestyle Swimming Skills According to Simple Sensory Learning - Hamid, Mwahb (Journal of Physical Education, 2016)
The importance of the research lies in individual learning patterns and their role in helping individual female students learn swimming skills. The problem of the research lies in answering the following question: what is the best learning style for learning freestyle swimming in third year female students of physical education and sport sciences college for women/ university of Baghdad? The research aims at identifying sensory learning patterns in the subjects of the research as well as classifying the students according to their Patten and finding the differences in learning some basic skills in freestyle swimming. The researcher hypothesized variances in sensory learning patterns and differences in learning freestyle swimming skills. The subjects were (97) third year female studentsof physical education and sport sciences college for women/ university of Baghdad. The subject was divided into four groups; visual students group (31), auditory students group (19), performance students group (40) and writing students group (7). The data was treated using proper statistical operations. The results showed performance students group was better than the other three groups. Visual students group developed in 10m freestyle swimming and gliding skills better than auditory and writing students groups. The researcher recommended that teachers should encourage using teaching aids for all learning patterns to improve learning and teaching